2018
DOI: 10.18632/oncotarget.25126
|View full text |Cite
|
Sign up to set email alerts
|

Role of tumor microenvironment in ovarian cancer pathobiology

Abstract: Ovarian cancer is the fifth most common cancer affecting the female population and at present, stands as the most lethal gynecologic malignancy. Poor prognosis and low five-year survival rate are attributed to nonspecific symptoms and below par diagnostic criteria at early phases along with a lack of effective treatment at advanced stages. It is thus of utmost importance to understand ovarian carcinoma through several lenses including its molecular pathogenesis, epidemiology, histological subtypes, hereditary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 161 publications
0
44
0
Order By: Relevance
“…This function of CCL14 plays an important anticancer role in OC, since a study demonstrated that there are a large number of macrophages and T lymphocytes in the OC microenvironment (44). Other studies reported that in OC, macrophages and T lymphocytes upregulate the expression levels of CCR1 and CCR5 receptors, which creates an antitumor immune environment leading to the necrosis of OC cells (45,46). Furthermore, another study investigating multiple myeloma demonstrated that when CCL14 binds to CCR1 and CCR5, it can lead to chemoattraction and recruitment of macrophages, which promotes proliferation by activating the PI3K-AKT, MAPK/ERK, JNK and p38MAPK pathways (42).…”
Section: Discussionmentioning
confidence: 99%
“…This function of CCL14 plays an important anticancer role in OC, since a study demonstrated that there are a large number of macrophages and T lymphocytes in the OC microenvironment (44). Other studies reported that in OC, macrophages and T lymphocytes upregulate the expression levels of CCR1 and CCR5 receptors, which creates an antitumor immune environment leading to the necrosis of OC cells (45,46). Furthermore, another study investigating multiple myeloma demonstrated that when CCL14 binds to CCR1 and CCR5, it can lead to chemoattraction and recruitment of macrophages, which promotes proliferation by activating the PI3K-AKT, MAPK/ERK, JNK and p38MAPK pathways (42).…”
Section: Discussionmentioning
confidence: 99%
“…In this process, polarized epithelial cells change their phenotype to motile mesenchymal cells. The downregulation of epithelial markers, such as E-cadherin, is replaced by the upregulation of mesenchymal markers such as vimentin, Slug, Snail, fibronectin, zinc-finger E-box binding homeobox 1 (ZEB1), ZEB2, and α-smooth muscle actin, allowing cells to migrate and invade [ 61 , 66 , 67 ]. These changes correlate with metastasis, recurrence, chemoresistant tumors, and poor outcome.…”
Section: Multifaceted Nature Of Macrophages In the Tmementioning
confidence: 99%
“…Ovarian cancer is the fifth leading cause of cancer-related deaths in women in the United States, and has a low survival rate, due in part to the frequent late stage at diagnosis [1,2]. Despite aggressive surgical debulking and first-line platinum-based therapy, a~70% relapse rate is observed, attributable to chemoresistance and peritoneal metastasis [1].…”
Section: Introductionmentioning
confidence: 99%